Social support and modelling in relation to physical activity and outdoor play in preschool chil-dren - Marzi, Isabel; Boxberger, Karolina; Schmidt, Steffen C.E.; Niessner, Claudia; Demetriou, Yolanda; Woll, Alexander; Reimers, Anne Kerstin (Abstractbook of the 15th annual meeting and 10th conference of HEPA Europe, 2019)
Purpose: Physical activity during early childhood is a precondition for healthy development and active living throughout life. However, few studies have focused on the role of social environmental behaviours of parents, peers, and siblings related to physical activity and outdoor play in preschool children. Thus, the aim of this study was to assess the relationships of social modelling and social support and physical activity in and outside of sports clubs and outdoor play in a nationwide sample of preschool boys and girls from Germany. Methods: 519 preschool children aged 4 to 6 participated in the German nationwide ‘MoMo’ Wave 1 cohort-study between 2009 and 2012. By using the validated MoMo-PAQ, the participants and their parents provided self-reported data on social support, social modelling, and domain-specific physical activity behaviour (physical activity in sports clubs, leisure time physical activity outside of sports clubs, outdoor play, physical activity at the preschool, and active commuting). Results: The results reveal that parental, peer, and sibling support and social modelling are related to preschool boys’ and girls’ physical activity in different domains. Differences were found between boys and girls. Parental support was particularly relevant for physical activity in sports clubs, and peer support was relevant for outdoor play. Parental modelling was only related to physical activity outside of sports clubs: Maternal modelling was a positive correlate in girls and paternal modelling in boys, respectively. Sibling and peer modelling were especially relevant for physical activity in sports clubs. Conclusions: In summary, the results were heterogeneous regarding types and providers of support and modelling behaviour. Thus, different providers and types of support should be targeted in physical activity promotion programs for preschool children. Support/Funding Source: This work was supported by the Federal Ministry of Education and Research [01ER1503] within the research program ´long-term studies` in public health research. It has been developed within the Motorik-Modul Longitudinal Study (MoMo) (2009 – 2021): Physical fitness and physical activity as determinants of health development in children and adolescents.
Keywords: exercise; child; parents; social environment; Germany; child care